Brainstem Auditory Evoked Potentials and Visual Potentials in Kawasaki Disease: An Observational Monocentric Study - Maggio, Maria Cristina; Corsello, Giovanni; Salvo, Giuseppe; Puma, Domenico Giuseppe; Cimaz, Rolando (Frontiers in Pediatrics, 2020)
Background: Kawasaki Disease is a systemic vasculitis, particularly involving coronary arteries. Rare involving of other vascular districts is described, as central nervous system arteries, leading to a vasculitic neuropathy. Sensorineural hearing loss and alterations of evoked potentials are uncommonly reported complications. Methods: In an observational monocentric study, 59 children (37 males; 22 females; mean age: 2.7±2.2 years) with documented Kawasaki Disease were enrolled. No risk factors for hearing loss and/or neurological impairment were identified in the cohort. Brainstem auditory evoked potentials and visual evoked potentials were correlated with clinical, haematological and radiological data, evaluated in the acute phase of the Kawasaki Disease, and during the follow up. Results: Evoked potentials were altered in 39/59 patients (66%): of these, 27/39 (69%) showed altered IV and V waves and/or III-V interwave latencies of brainstem auditory evoked potentials; 4/39 (10%) showed pathological visual evoked potentials; 8/39 (21%) had abnormalities of both brainstem auditory evoked potentials and visual evoked potentials. No permanent deafness was reported. Conclusion: Abnormalities in visual evoked potentials were not significantly correlated with coronary artery lesions; however, the presence of abnormalities of brainstem auditory evoked potentials were associated with the risk of coronary artery lesions, alone or in association with pathological brainstem auditory evoked potentials.